Distortion and dissatisfaction with body size per the demographic and academic characteristics and the nutritional status of university students - Dos Santos, Adrielly [UNESP]; da Silva, Wanderson Roberto [UNESP]; Santana, Moema de Souza [UNESP]; Campos, Juliana Alvares Duarte Bonini [UNESP] (Editora Cubo, 2020)
To identify the prevalence of distortion and dissatisfaction with the body size of Brazilian university students, and establish their relationship with the demographic and academic characteristics and the anthropometric nutritional status. The sample consisted of students from a public university in the state of São Paulo. The Figure Rating Scale (FRS) for Brazilian adults was used as an instrument. The participants selected the figure that corresponded to the current body and another one for the desired body. The prevalence of distortion and dissatisfaction with body size was calculated with 95% confidence interval (95% CI). The association between the variables was evaluated by the Chi-Square Test (χ2). The significance level of 5% was adopted. A total of 356 students (women=71.63%) with a mean age of 20.95 (SD=2.55) years participated. The prevalence of distortion and dissatisfaction with body size was 73.03% (95% CI=68.23–77.83) and 79.49% (95% CI=75.3–83.68), respectively. There was a high prevalence of distortion with body size among individuals with low weight (χ2=9.523, p=0.009). Students who distorted the body size (52.31% [95% CI=47.12–57.50]) underestimated their body size. The type of distortion was related to sex (χ2=26.35, p<0.001), physical activity (χ2=4.51, p=0.034), use of supplements (χ2=4.62, p=0.032), and the anthropometric nutritional status (χ2=9.05, p=0.011). Students dissatisfied with the body (58.66% [95% CI=52.92–64.40]) wished to reduce the body size. The type of dissatisfaction was related to sex (χ2=5.79, p=0.016) and anthropometric nutritional status (χ2=89.83, p<0.001). The prevalence of body size underestimation was higher among men, students who practice physical activity, subjects using dietary supplements and underweight individuals. The wish to decrease body size was higher among women and overweight/obese individuals.
Keywords: Body Dissatisfaction; Body Distortion; Body Size; University Students